2018
DOI: 10.3390/molecules23040876
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate-Modified Gelatin Sponges Treated by Vacuum Heating as a Novel Scaffold for Bone Tissue Engineering

Abstract: Chemical modification of gelatin using epigallocatechin gallate (EGCG) promotes bone formation in vivo. However, further improvements are required to increase the mechanical strength and bone-forming ability of fabricated EGCG-modified gelatin sponges (EGCG-GS) for practical applications in regenerative therapy. In the present study, we investigated whether vacuum heating-induced dehydrothermal cross-linking of EGCG-GS enhances bone formation in critical-sized rat calvarial defects. The bone-forming ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…4-(4,6-Dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMT-MM) and N-methylmorpholine (NMM) were obtained from Tokyo Chemical Industry Co. Ltd. (Tokyo, Japan) and Nacalai Tesque Inc. (Kyoto, Japan), respectively. The AC-vhEGCG-GS was prepared according to previous methods 18) . Briefly, 0.07 mg of EGCG, 100 mg of gelatin, 27.5 μl of NMM, and 69.2 mg DMT-MM were mixed in 5 ml of MilliQ water at 23 o C. The dose of EGCG and gelatin determined in our previous study to result in superior bone formation was used 18,24) .…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…4-(4,6-Dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMT-MM) and N-methylmorpholine (NMM) were obtained from Tokyo Chemical Industry Co. Ltd. (Tokyo, Japan) and Nacalai Tesque Inc. (Kyoto, Japan), respectively. The AC-vhEGCG-GS was prepared according to previous methods 18) . Briefly, 0.07 mg of EGCG, 100 mg of gelatin, 27.5 μl of NMM, and 69.2 mg DMT-MM were mixed in 5 ml of MilliQ water at 23 o C. The dose of EGCG and gelatin determined in our previous study to result in superior bone formation was used 18,24) .…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…Consequently, numerous delivery systems have been developed to provide localized release of these therapeutic agents in biomedical engineering 17) . For EGCG, various techniques have been developed to retain or deliver EGCG in the affected areas; these techniques include chemical bonding to polymers 14,16,18) , layer by layer technique 19) , hydrophobic and/or hydrogen bonding 20,21) , EGCG-coating associated with Na + -mediated physical self-assembly 22) and oxidative polymerization 3) , and en-capsulation in drug carriers 23) . Although our understanding of the application of this molecule in bone regenerative therapy remains limited when compared with that in other medical fields, we previously found that gelatin sponges chemically modified with EGCG using an aqueous chemical synthesis method (hereafter designated as AC-EGCG-GS) induced superior bone formation in critical-sized bone defects (4.2 mm of diameter) in mouse calvaria 14) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gelatin, denatured collagen, has been widely utilized as a substrate for biomaterials and drug carriers [25][26][27]. Various groups, including our own group, have utilized this protein as a controlled release carrier for polyphenol [28], growth factors, and antibiotics [27]. A vacuum-heating technique (dehydrothermal treatment: DHT) has been utilized to promote intermolecular bonding based on esterification between the carboxyl and hydroxyl groups in polymers [29].…”
Section: Introductionmentioning
confidence: 99%